A study on the effectiveness and safety of interventional embolization using drug-loaded microspheres in combination with sorafenib and envafolimab for intermediate and advanced renal cell carcinoma - Chen, Cheng; Shen, Yanfeng; Ma, Yanhong; Zhang, Yingying; Zhang, Shuyan; Su, Na; Guo, Hefei; Guo, Yapeng; Zhang, Xuehui; Liu, Xianming; Zhang, Suhua; Li, Shuai; et al. (Frontiers in Oncology, 2025)
ObjectiveTo investigate the effectiveness and safety of drug-loaded microsphere interventional embolization (D-TAE) in conjunction with sorafenib and envafolimab in the management of intermediate and advanced renal carcinoma.Methods120 cases of intermediate and advanced renal cell carcinoma cured in the Oncology Department of our hospital from January 2022 to December 2023 were selected. Individuals in the combination group received D-TAE paired with sorafenib and envafolimab. Individuals in the D-TAE group received only D-TAE. The clinical data, clinical efficacy, vascular endothelial growth factor (VEGF), carcinoembryonic antigen (CEA), carbohydrate antigen 125 (CA125), mortality, progression-free survival time (PFS), objective tumor response rate (ORR) and tumor control rate (DCR) and adverse reactions were compared in both groups.ResultsThe proportion of individuals with ORR and DCR in the combination group was greatly increased compared to that in the D-TAE group (P <0.05). After 1 week and 1 month of treatment, the serum VEGF levels in both groups showed a great decrease compared to pre-treatment levels (P<0.05), with the combination group demonstrating notably lower serum VEGF levels than the D-TAE group (P<0.05). Following treatment, serum CA125 and CEA levels in both groups experienced a great decrease compared to pre-treatment levels, with the combination group showing notably lower levels than the D-TAE group (P<0.05). Additionally, the mortality rate in the combination group was greatly lower than that in the D-TAE group, and the PFS was greatly increased in the combination group compared to the D-TAE group (P<0.05). In addition, the observed adverse reactions included gastrointestinal reactions, liver and kidney damage, myelosuppression and rash. Overall, the incidence of adverse reactions in the combination group was greatly decreased than that in the D-TAE group (P<0.05).ConclusionDrug-loaded microsphere interventional embolization combined with sorafenib and envafolimab has certain efficacy and acceptable safety in treating intermediate and late-stage renal tumor, providing a new treatment option for patients with renal cell carcinoma.